Work Ideologies and Constructions of Disability in the Puerto Rican Context - Báez-Lebrón, Maribel (Revista Electrónica Educare, 2015)
This paper summarizes a study conducted in 2012 with the purpose of analyzing work ideologies constructed by the media regarding subjectivity towards disability during the 2009 implementation of the Special Act Declaring a State of Fiscal Emergency to Save the Credit of Puerto Rico (Act No. 7).  Through a qualitative design and the manifest and latent content analysis techniques, and using the Disability and Human Subjectivity Models as the theoretical framework, a total of four hundred and sixty-seven (467) newspaper articles published between February and October 2009 was reviewed.  Results demonstrate that only fourteen articles (3%), which constitute the units of analysis, made reference, directly or indirectly, to disability.  The content of these articles is based on an ideology that excludes people with disabilities from social participation because they are considered incapable, unfit and worthless.  The disability and human subjectivity models that predominate are the socio-political and positional-existential ideology, respectively.  It was concluded that the work ideologies constructed by the media regarding subjectivity towards disability are used to exclude people with disabilities from the job market, without recognizing their power and ability of being and doing.